Using a four-dimensional geographical information system to visualise the environmental impact of smog. - Sandison, Daniel C. (Curtin University, 1999)
This research was developed to investigate the potential environmental impacts of poor air quality in Perth. This involved improving existing vegetation maps (through satellite image analysis techniques) for biogenic or forest emissions as a precursor to smog in Perth. Further, to visualise potential environmental impacts associated with poor air quality, a four- dimensional (volumetric over time) animation was created which clearly shows the path and extent of smog in Perth throughout an entire day.Computer mapping of vegetation using Landsat TM data was performed to create an updated inventory of forest types in Perth as input into a photochemical smog model. By improving the inventory of forest cover, the Department of Environmental Protection (DEP) in Perth can calculate up to date biogenic emission estimates for the photochemical smog model.Outputs from the DEP's photochemical smog model were integrated into a Geographical Information System (GIS) and subsequently visualised to show plume movement and potential environmental impact. Two datasets (nitrogen oxides and ozone) were provided to investigate the volumetric and dynamic temporal movement of photochemical smog in Perth on one day, March 16, 1994.Nitrogen oxide sources can range from industry and petroleum refining to motor vehicle exhaust emissions, and are a major precursor to photochemical smog (ozone) formation in Perth. Natural emission sources (forest or biogenic emissions) can also be an important contributing factor to the photochemical smog mix in Perth. Biogenic emissions are comprised of Reactive Organic Chemicals (ROC) or Volatile Organic Compounds (VOC) which act as a catalyst to aid the nitrogen oxide conversion to ozone.Three-dimensional and four-dimensional GIS techniques were used to highlight both plume movement and environmental impact. These two sets of visualisations have differing chemical levels (higher and lower, respectively) to show movement and interaction effectively. Visualisation of the chemicals allows for a greater understanding of the mostly invisible chemical movement over the course of a day and its potential impact to humans and vegetation.The spatial and temporal interaction of the plumes was investigated by creating a series of animations that can be viewed over the Internet. By using multimedia capabilities, these results can be easily distributed to a wide range of decision makers and people generally interested in smog in Perth.